Avaliação de assinaturas moleculares relacionadas à processos redox em mulheres com câncer de mama - Santos, Letícia Lopes Dantas (2024)
The most prevalent type of cancer affecting the global female population is breast cancer, emerging as one of the leading causes of death among women. In this context, clinical, pathological, and biological data are employed by healthcare professionals to predict clinical outcomes. However, the development of new strategies for cases of breast cancer (BC) with unfavorable prognosis is imperative. This thesis highlights that redox imbalance can be addressed as a molecular prognostic signature for women with BC. Comprising three chapters, this thesis aims to evaluate molecular signatures related to redox processes in women with BC. The first chapter of the thesis provides a literature review on the key topics related to the proposed objective. The second chapter consists of a scientific article investigating the wavenumbers of the infrared spectrum obtained by ATR-FTIR and their relationship with the levels of redox status markers in the blood of women with HER2+, HER2- BC, and benign breast disease (BBD). The results indicate that HER2+ BC cases differ from HER2- BC and BBD cases based on serum antioxidant capacity [HER2+ BC vs. HER2- BC (AUC = 0.818; specificity = 81.82%; sensitivity = 66.67%); HER2+ BC vs. BBD (AUC = 0.875; specificity = 75%; sensitivity = 83.33%)]. Furthermore, biochemical alterations in the serum due to antioxidant deficiency are linked to a distinctive fingerprint in the infrared spectrum obtained by ATR-FTIR. The third chapter comprises a scientific article evaluating the quantification of free thiol (sulfhydryl, R-SH) using serum samples from women with metastatic BC, non-metastatic BC, BBD, and healthy controls. The quantification of free R-SH demonstrated a notable reduction in women with metastatic BC (p = 0.018). In summary, it was possible to conclude that the analysis of systemic redox status in blood samples proves to be of great value for the development of less invasive tools for screening, monitoring, and prognostication of BC.